THE RETURN OF THE SHEEP INDUSTRY PRODUCTIVE SCENARIO OF RIO GRANDE DO SUL - Ávila, Viviane Schons de; Fruet, Ana Paula Burin; Barbieri, Marcieli; Bianchini, Nadia Helena; Dörr, Andréa Cristina (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
This review aims to conduct a historical analysis of the production chain of sheep in the Rio Grande do Sul, for this purpose we studied the market before the crisis laneira, the late 80s, and the return of productivity after the change in the focus of production. The sheep were introduced in Brazil in the sixteenth century, but only in the twentieth century the activity generated economic development in Rio Grande do Sul, in this period the main product was exploited wool. However, in the late 80s was the beginning of the crisis in the sector laneiro, mainly caused by an increase in inventories of wool from Australia, the marketing of synthetic fabrics and global crises and collapses. Currently identified is the return of the sheep production industry dedicated to meat eating as a result of factors such as the increased purchasing power of the population and adapt to new consumer habits that lead to appreciation for sheep meat. The trends for this market are promising. However, there are some barriers to growth, as the disorder of the sector and the lack of standardization of products. For the state to become major producer of sheep meat is necessary to organize the sector, from production to distribution channels.